Seminal vesicle fistula: a rare pathology in complicated Crohn's disease. Issue 5 (6th May 2022) - Thompson, Jessica; Patel, Amit; Nicholson, Gary
Abstract : This case report describes a patient with complicated Crohn's disease who presented to a routine gastroenterology clinic complaining of increasing white discharge from a chronic perianal abscess. MRI of the perineum established the diagnosis of a seminal vesicle fistula connecting to the perianal skin. He was treated conservatively, with optimisation of his Crohn's disease medication regime. Seminal vesicle fistulation is a rare pathology.